Does Maternal Obesity Affect Preterm Birth? Documentary Cohort Study of Preterm in Firstborns-Silesia (Poland) - Karolina Sobczyk; Tomasz Holecki; Joanna Woźniak-Holecka; Mateusz Grajek (MDPI AG, 2022)
In addition to low birth weight and intrauterine growth restriction, prematurity is a major problem in modern neonatology. The etiology of premature delivery is multifactorial, but maternal obesity has been indicated as an important risk factor for preterm birth. This study aimed to assess the relationship between early pregnancy body mass index (BMI) and the risk of preterm delivery according to gestational age. In the cohort of 2794 firstborns, preterm deliveries accounted for 9.1%. Of all deliveries, 16, 48, and 189 were classified as extremely preterm, very preterm, and moderately preterm deliveries, respectively. The risk of extremely, very, and moderately preterm deliveries increased with the increasing BMI, with the highest overweight and obesity-related risk for extremely and very preterm delivery. The rate of extremely and very preterm delivery among normal-weight women (BMI 18.5 ≤ 25) was 1.8%, while that among overweight and obese women (BMI ≥ 25) was 2.36%. The rate of all preterm deliveries (22 ≤ 37 weeks) was 8% for normal-weight women and 10.3% for overweight and obese women. Compared with normal-weight women, the adjusted odds ratio (95% CI) for preterm delivery in overweight and obese women was 1.33 (0.98-1.79). In Poland, being overweight and obese during pregnancy was associated with an increased risk of preterm delivery, especially extremely and very preterm delivery. This relationship should be assessed in other populations.